Teaching Representations of Competency-Based Education. A Case Study - Covarrubias-Papahiu, Patricia (2016)
The aim of this research was to know how the Competency-Based Education (CBE) approach is represented by professors who are part of the professional education of psychologists, and the challenges and implications of, in their opinion, incorporating it in the classroom practice. Therefore, a research was conducted to know the type of representations and meanings that they give to the approach for its approval or rejection, whether they apply it in their teaching practice, and the kind of competencies that thThe aim of this research was to know how the Competency-Based Education (CBE) approach is represented by professors who are part of the professional education of psychologists, and the challenges and implications of, in their opinion, incorporating it in the classroom practice. Therefore, a research was conducted to know the type of representations and meanings that they give to the approach for its approval or rejection, whether they apply it in their teaching practice, and the kind of competencies that they want to promote among their students for their professional practice. This case study that counts with the collaboration of professors from the Psychology Specialty delivered in one of the university campuses of the UNAM University, used a qualitative methodology with a descriptive and interpretative approach that used semi-structured interviews as a data collection tool. The most distinctive results demonstrate that, concerning the heterogeneous nature of the disclosed representations among the interviewed professors, the balance falls in favor of the teachers that do not approve and/or use the competency-based approach. Their most consistent arguments to reject it included the unfamiliarity with the approach, or the difficulty to put it into practice, and/or its connection with neo-liberal, functionalist and business policies. However, the professors that accept and apply it, value the development of attitudes considered by the approach, especially those with a humanistic view towards the education of psychologists; while others appreciate how it promotes the necessary abilities for an efficient professional performance.